Influence of Social Media Marketing on Online Purchase Intention of Smartphone Buyers in the Maharashtra State of India - Pritam, Kumar (2025)
With the rise of social media, everyone can become a content creator in today's interconnected world. So, participation in social media affects consumers' propensity to buy. Nevertheless, this study is necessary since the engagement of social media greatly influences purchasing decisions, and this shift in communication poses new possibilities and problems for organizations. The main aim of this research was to determine the effects of using social media marketing, which could ultimately lead to an evaluation of the online purchase intention of people in the Maharashtra state of India who are interested in purchasing a smartphone. The purpose of this research was to investigate the impact that social media marketing activities (interaction, accessibility, social influence, and cost-efficient) through the mediating role of electronic word-of-mouth (e-WOM) have on the likelihood that smartphone purchasers in the Maharashtra state of India will make an online purchase. The study used a quantitative research design and a non-probability convenience sampling technique to achieve its empirical objectives. A total of 384 surveys were administered in order to compile the results. For descriptive statistics, we utilized SPSS version 23.0 and for inferential statistics, we used Smart PLS version 4.1.0. Results from the data analysis revealed positive significant relationship between interaction, accessibility, social influence, and cost-efficient and purchase intention of smartphone online buyers who use social media through the mediating role of electronic word-of-mouth (e-WOM). The study's findings indicate that it is advisable for the business to integrate social media marketing into its comprehensive strategy, establish and oversee online communities to engage with current and prospective customers, and implement advertising and promotional campaigns on social media platforms. Furthermore, the study's limitations and possible directions for further research were highlighted.